Pollen counts from IODP Site 339-U1385 - Stéphanie Desprat; Teresa Rodrigues; Gauthier Guillem; Sánchez Goñi Maria Fernanda; Qiuzhen Yin; Joan O Grimalt (PANGAEA, 2024)
The published data come from the analysis of pollen and spores contained in sediments from IODP site U1385 (Expedition 339) retrieved from the Iberian margin. These data cover the interval from 345 to 307 ka, which includes the MIS 9e. The data table provides the pollen counts.